Kolaborasi UMKM dan Startup Digital Di Kota Makassar dan Dampaknya terhadap Pengelolaan Keuangan - Nurjannah Nurjannah; Sri Utami (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Collaboration Between MSMEs and Digital Startups in Makassar City and Its Impact on Financial Management and Business Growth. The purpose of this study is to examine the collaboration between MSMEs and startups in Makassar City, which includes face-to-face dialogue, building trust, commitment to processes, and shared understanding. This study uses a qualitative method with a descriptive approach to analyze and interpret the data obtained through observations and interviews. The results of this study, conducted on MSMEs in Makassar City, show that collaboration with digital startups has a significant impact on financial management and business growth. This impact is achieved through the utilization of digital technology, such as increased efficiency, the adoption of new technologies, a stronger focus on financial analysis, easier preparation of financial reports, improved access to financial services, the use of innovative technologies, enhanced product quality, and expanded market reach.